Plant-derived polyphenolic compounds for managing schizophrenia: mechanisms and therapeutic potential - Ji, Xiaolin; Chai, Jianbo; Zhao, Sihan; Zhao, Yonghou (Frontiers in Pharmacology, 2025)
Schizophrenia is recognized as a severe mental disorder that is marked by psychotic symptoms, which frequently result in profound social stigma and severely hinder occupational functioning. The current research explores the biological activities of plant-derived polyphenolic compounds, specifically highlighting curcumin and epigallocatechin gallate (EGCG), along with other plant polyphenols. Importantly, both curcumin and EGCG demonstrate neuroprotective properties via various mechanisms, such as antioxidant and anti-inflammatory effects, neurotransmitter modulation, improvement of mitochondrial function, and stimulation of neurogenesis. These mechanisms play a role in reducing the pathological symptoms of schizophrenia and enhancing cognitive abilities, ultimately improving the overall quality of life for patients. Considering the difficulties linked to existing pharmacological therapies, which frequently present constraints and unwanted adverse effects, plant-derived polyphenolic compounds have attracted interest as potential therapeutic alternatives. These plant compounds hold the potential not only to alleviate the symptoms of schizophrenia but also to enhance cognitive function. They may achieve this through various mechanisms, such as boosting antioxidant defenses, reducing neuroinflammation, balancing neurotransmitters, increasing brain-derived neurotrophic factor (BDNF) levels, and enhancing mitochondrial function. Numerous studies involving animals have shown that polyphenols sourced from plants can markedly increase the levels of brain-derived neurotrophic factor (BDNF), leading to improvements in neurodevelopmental disorders. These compounds also help restore mitochondrial function by replenishing ATP levels and boosting systemic antioxidant capacity through the reduction of serum malondialdehyde (MDA) levels, while simultaneously enhancing the activity of antioxidant enzymes, including superoxide dismutase (SOD). Additionally, they have been reported to lower inflammatory markers, particularly interleukin-6 (IL-6). Moreover, polyphenols play a significant role in regulating neurotransmitter levels by decreasing the concentrations of dopamine and glutamate. Moreover, ongoing research into the structure, classification, and characteristics of polyphenolic compounds, alongside advancements in nanotechnology and metabolic regulation, has opened up innovative delivery strategies for these compounds. Such developments present new opportunities for creating effective and low-toxicity natural derivatives. Future studies are anticipated to support a transition from conventional “single-target” approaches to more comprehensive “multi-target network regulation” therapeutic strategies.